Occult/Paranormal Bibliography: An Annotated List of Books Published in English, 1976 Through 1981 - Clarie, Thomas C. (Scarecrow Press, 1984)
English-language books published or reissued between 1976-1981. Arranged alphabetically by authors. Asterisks indicate excellence. Author, title, and subject indexes.
Keywords: Bibliography; Bibliography; Parapsychology; Occultism; dept.lib; faculty_collection